2003
DOI: 10.1001/archneur.60.5.737
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis and Prophylactic Therapy for Presymptomatic Chinese Patients With Wilson Disease

Abstract: We conclude that presymptomatic DNA diagnosis and zinc therapy are effective treatment of patients with WD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 12 publications
0
27
2
1
Order By: Relevance
“…We could not find any significant difference between Arg778Leu homozygosity and heterozygosity with regard to the mean age of onset of symptoms, although Wu et al [7] have reported that the average age of onset in 18 Chinese homozygotes was significantly lower than that in 11 Chinese compound heterozygotes for Arg778Leu. However, the number of patients with hepatic manifestations among those carrying Arg778Leu mutation was significantly greater than that among patients without the mutation.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We could not find any significant difference between Arg778Leu homozygosity and heterozygosity with regard to the mean age of onset of symptoms, although Wu et al [7] have reported that the average age of onset in 18 Chinese homozygotes was significantly lower than that in 11 Chinese compound heterozygotes for Arg778Leu. However, the number of patients with hepatic manifestations among those carrying Arg778Leu mutation was significantly greater than that among patients without the mutation.…”
Section: Discussioncontrasting
confidence: 80%
“…However, some asymptomatic patients do not receive effective treatment before irreversible injury is present. Genetic diagnosis may detect presymptomatic patients, in whom initiation of prophylactic therapy can effectively prevent the otherwise inevitable hepatic and neurological injury [6,7] . Mutations in the P-type ATPase (ATP7B, MIM#277900) gene are responsible for WD.…”
Section: Introductionmentioning
confidence: 99%
“…17 The second most frequent mutation was p.Ile1148Thr (9.59%) in exon 16, but the other hot mutation, p.Thr935Met in exon 12, was detected in only one allele, which differs from the published results of earlier research. 18 The p.His1069Gln mutation is the most common mutation in European populations, [19][20][21] but it was not found in our patients. All other mutations were identified at a low frequency.…”
Section: Discussioncontrasting
confidence: 58%
“…It produces a negative copper balance by blocking the intestinal absorption of copper, and it induces hepatic metallothionein synthesis, which sequesters the additional toxic copper. All the presymptomatic patients should be treated prophylactically, since the disease is close to 100% penetrant 10,11 . Our case was treated with oral zinc (as zinc acetate) in high doses (1mg/kg/ dose 8 hourly) and trihexyphenidyl 4mg 8 hourly.…”
Section: Discussionmentioning
confidence: 99%